1994
DOI: 10.1037/0882-7974.9.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Long-term retention of skilled visual search: Do young adults retain more than old adults?

Abstract: Young and old Ss received extensive consistent-mapping visual search practice (3,000 trials). The Ss returned to the laboratory following a 16-month retention interval. Retention of skilled visual search was assessed using the trained stimuli (assessment of retention of stimulus-specific learning) and using new stimuli (assessment of retention of task-specific learning). All Ss, regardless of age group, demonstrated impressive retention. However, age-related retention differences favoring the young were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 54 publications
4
19
0
Order By: Relevance
“…Older adults have shown greater improvements than younger adults in reaction time in the task-switching 34 and in consistent-mapping visual search paradigms. [35][36][37] Although older adults did not show greater improvement when working-memory load was high, 34 nor did they show as much stimulus-specific learning as did younger participants, 36 older adults retained what they learned up to 16 months. 37 In the present study, older pilots conceivably improved their reactions to oncoming traffic by learning task switching and visual search strategies helpful to performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults have shown greater improvements than younger adults in reaction time in the task-switching 34 and in consistent-mapping visual search paradigms. [35][36][37] Although older adults did not show greater improvement when working-memory load was high, 34 nor did they show as much stimulus-specific learning as did younger participants, 36 older adults retained what they learned up to 16 months. 37 In the present study, older pilots conceivably improved their reactions to oncoming traffic by learning task switching and visual search strategies helpful to performance.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Although older adults did not show greater improvement when working-memory load was high, 34 nor did they show as much stimulus-specific learning as did younger participants, 36 older adults retained what they learned up to 16 months. 37 In the present study, older pilots conceivably improved their reactions to oncoming traffic by learning task switching and visual search strategies helpful to performance. Greater improvement among older adults has rarely been reported in longitudinal studies employing paper-and-pencil neuropsychological or intellectual ability tests, 31,32 but see reference 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Fisk and Hodge (1992) measured retention at intervals up to 1 year after practice, and found that the performance characteristics of automatic processes were well maintained even after long periods of disuse. Interestingly, Fisk, Hertzog, Lee, Rogers, and Anderson (1994) found that across experiments there was a decline in search conditions that required information coordination. These findings indicate that although the automatic processes may not have decayed, the strategic, controlled processing aspects of the task did.…”
Section: Principlementioning
confidence: 99%
“…The contribution of memory-based processing to speed-ups with practice has been shown in a wide range of skill acquisition tasks, including alphabet arithmetic (e.g., Klapp, Boches, Trabert, & Logan, 1991;Wilkins & Rawson, 2010, pound arithmetic (described below; e.g., Rickard, 1997;Touron et al, 2004), multiplication (e.g., Rickard, Lau, & Pashler, 2008), visual search (e.g., Fisk, Hertzog, Lee, Rogers, & Anderson-Garlach, 1994), noun-pair look-up (e.g., Rogers et al, 2000;Touron & Hertzog, 2004a), lexical decision (e.g., Grant & Logan, 1993;Logan, 1988), and numerosity judgments (e.g., Jenkins & Hoyer, 2000;Lassaline & Logan, 1993;Palmeri, 1997). Most relevant for present purposes, recent research has also established the contribution of memory-based processing to speed-ups with practice in syntactic and semantic processes during reading tasks (Rawson, 2004(Rawson, , 2010Rawson & Middleton, 2009;Rawson & Touron, 2009).…”
Section: Early Theories Of Automaticity Involved Whatmentioning
confidence: 99%